How Technology Can Change Educational Research? Definition, Factors for Improving Quality of Education and Computational Bibliometric Analysis - Al Husaeni, Dwi Fitria; Al Husaeni, Dwi Novia; Nandiyanto, Asep Bayu Dani; Rokhman, Mauhibur; Chalim, Saefuddin; Chano, Jiraporn; Al Obaidi, Abdulkareem Sh. Mahdi; Roestamy, Martin (ASEAN Journal of Science and Engineering, 2024)
This study explains all factors relating to the definition and current research trends in how technology can improve education. This study explains how strategies are developed to create and improve the quality of education, including communication, the input of technology (such as IT, ICT, AI, AR, etc.), curriculum and education level, and the relationship between social studies, humanities, science, and industry, as well as management and facilities. We demonstrated current technology using social media, for educators to implement it to improve the teaching and learning process. Bibliometric and theoretical analysis, based on the Google Scholar database from 2018-2023, was used. The search results found 988 articles with the keywords of "Education Technology" AND "Indonesia". Research on educational technology in Indonesia has increased every year. 113 terms were found based on network visualization, which was divided into 6 clusters. The “Indonesia” term appeared 596 times and the term “education technology” appeared 133 times. Co-authorship analysis found 2035 authors have contributed. Completing this research leads to the creation of future research, determining what next research subjects can appear, especially in the field of education.